Inscription of a destination as a world heritage site and residents' perceptions. Issue 1 (2nd January 2019) - Md Noor, Shuhaida; Rasoolimanesh, S. Mostafa; Jaafar, Mastura; Barghi, Rabeeh
ABSTRACT: This paper investigates the differences between residents' perceptions toward tourism development in two rural tourism destinations, one of which has already been inscribed as a World Heritage Site (WHS). The effects of environmental and cultural attitudes, as well as individual economic gain and community gain on residents' positive and negative perceptions toward tourism development are compared in these two destinations using Weber's Theory. The findings of this study showed that positive perceptions, and community gain were highest, and negative perceptions the lowest with respect to tourism development in the WHS destination. This study makes a significant theoretical contribution to the resident perception literature by investigating the effects of WHS inscription on residents' perceptions toward tourism development.